The Influence of Service Quality on Customer Satisfaction at PT. Krakatau Bandar Samudera - Winarto, Puji; Ruswanti, Endang (Journal of Current Research In Multidisciplinary, 2025)
This study aims to discuss the dimensions of service quality consisting of tangibles, reliability, responsiveness, assurance, and empathy towards customer satisfaction variables. This study used questionnaires distributed to 96 customer respondents of PT Krakatau Bandar Samudera, while the method used was multiple regression analysis using statistical software. The results of the analysis show that service quality variables influence customer satisfaction variables and there is a level of importance of the variables studied on customer satisfaction. The assurance and empathy variables have a significant positive effect on customer satisfaction. The results of the study stated that the empathy variable has a greater influence value compared to the assurance, responsiveness, reliability, and tangibles variables in influencing customer satisfaction. Therefore, it can be concluded that the rise and fall of port service quality can affect customer satisfaction.